Nitrogen-corrected apparent metabolizable energy and standardized ileal amino acid digestibility of Brazilian DDGS for broilers - Bruno F. de Almeida; Ideraldo L. Lima; Kelly M.M. Dias; Carlos H. Oliveira; Kaique M. Gomes; Artur M. Ribeiro; Brian P. Mike; Arele A. Calderano (Poultry Science, 2025)
Metabolism and digestibility trials were performed on broiler chickens to determine the nitrogen-corrected apparent metabolizable energy (AMEn) values and the standardized ileal amino acids digestibility (SIAAD) coefficients for broiler chickens of dried distiller’s grains with solubles (DDGS) from three Brazilian processors. The metabolism and digestibility trials were performed on 20-30 day old chickens, with total excreta method used to determine energy values and the ileal digesta collection method used to determine SIAAD coefficients. The data obtained was subjected to analysis of variance and the means were compared using the Tukey test at 5 % significance. The AMEn values were 2,408.70 kcal/kg for DDGS 1, 1,763.20 kcal/kg for DDGS 2, and 1,873.40 kcal/kg for DDGS 3, on dry matter basis. The DDGS 1 had the highest AMEn value (P < 0.05). Regarding the SIAAD coefficients, DDGS 1 had the highest values for arginine, histidine, leucine, cystine, and proline (P < 0.05). In conclusion, there is variation in the nutritional value of DDGS available in Brazil.